Pengaruh Model Pembelajaran Kooperatif Tipe Course review Horay Terhadap Hasil Belajar Fisika - Darmawati Darmawati; Kamaluddin Kamaluddin; Muhammad Ali (Jurnal Kreatif Online, 2021)
This research was conducted with the aim of knowing the effect of the Course Review Horay (CRH) cooperative learning model on the physics learning outcomes of class VIII students of MTs Negeri 1 Palu. This type of research was a quasi-experimental design with a non-randomized pretest-posttest control group. The population of this research was all students of class VIII MTs Negeri 1 Palu. The sampling technique used in this study was purposive sampling with the research sample being class VIII G as the experimental group and class VIII E as the control group. The instrument was a multiple choice test that has been validated by an expert validator. The physics learning result test obtained showed that the pretest average score of the experimental group was 43.95 and the control group was 42.05, while the posttest average score of the experimental group was 75.15 and the control group was 62.65. From the results of the t-test, it was found that there was an effect of student learning outcomes using the Course Review Horay (CRH) cooperative learning model on physics learning outcomes in class VIII students of MTs Negeri 1 Palu.